การเผยแพร่กับการตัดสินใจใช้นวัตกรรมเอ็นจีวีของผู้ใช้รถยนต์ในเขตกรุงเทพมหานคร - ภัคจิรา แบบแผน (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The purpose of this research was to study (1) the diffusion of NGV innovation to drivers, (2) the decision process of Bangkok drivers, (3) other factors affecting drivers’ decision to adopt NGV innovation. The study was qualitative research. In-depth interview with 3 officials of PTT Public Company Limited and 30 drivers who adopted NGV was used to collect the data. The findings of the research were as follows: The diffusion of NV innovation of PTT Public Company Limited was composed of 5 stages : 1. Stimulation 2. Initation or Introduction 3. Creation of the awareness of "The Safety" of NGV 4. Encouraging for decision to adopt 5.Post adoption. The decision process to adopt NGV innovation of the drivers was composed of 3 stages : 1. Seeking for solution 2. Interest 3. Adoption Other factors affecting decision to use NGV were : 1. Characteristics of NGV which were composed of (1.) relative advantage (2.) complexity (3.) observability 2. Characteristics of drivers which were composed of (1.) income and level of living (2.) career